(3GdMeGjI GdLfGFjI ddeGd GdYGe (B/ s - (3fGUQ Nda HNjJs; (3GMeO YhV HdGd s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3gPg GdQSGdI bO SQOJ GdMeGjI GdLfGFjI ddeGd GdYGe efP GdYUQ GdaQYhfi MJi YUQfG GdMGdi hfLO Cf gfGc MeGjI cHjQI ai eUQ GdaQYhfjI hai YUQ GdHWGdeI hYUQ GdOhdI GdESdGejI GdChdi hHNGUI ai YUQ GdQShd (B((3U(B) (3hai YUQ GdNdaGA GdQGTOjf hcPdc ai GdYUQ GdMOjK hJfGhdJ Jdc GdQSGdI ebheGJ GdMeGjI GdLfGFjI ddeGd GdYGe ef MjK GdWHjYI GdbGfhfjI dLQGFe GdeGd GdYGe heOi GQJHGWgG HLQGFe Cef GdOhdI ShGA ef GdNGQL Ch ef GdOGNd s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2008s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B347-375s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdMeGjI GdLfGFjIs; (3GdeGd GdYGes; (3GdehXa GdYGes; (3GdGNJdGSs; (3GdJQHMs; (3GdGSJjdGAs; (3LQGFe GdGgeGds; (3GdGNdGd GdYeOis; (3YbhHI GdGYOGes; (3GdeUGOQIs; (3GdCYPGQ GdeYajIs; (3YbhHI GdYRds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs